Micro-/Nano-Structures Fabricated by Laser Technologies for Optoelectronic Devices - Yi, Jian; Zhou, Hao; Wei, Wei-Hua; Han, Xing-Chen; Han, Dong-Dong; Gao, Bing-Rong (Frontiers in Chemistry, 2021)
Due to unique optical and electrical properties, micro-/nano-structures have become an essential part of optoelectronic devices. Here, we summarize the recent developments in micro-/nano-structures fabricated by laser technologies for optoelectronic devices. The fabrication of micro-/nano-structures by various laser technologies is reviewed. Micro-/nano-structures in optoelectronic devices for performance improvement are reviewed. In addition, typical optoelectronic devices with micro-nano structures are also summarized. Finally, the challenges and prospects are discussed.